The Holy Spirit, Eco-Justice, and an African Lutheran Response to Ecological Peril - Lugazia, F. K. (Dialog, 2016)
In response to the environmental degradation that is taking place right now in much of Africa—and in light of a traditional African emphasis on interdependence—this article seeks to provide an African Lutheran “eco-pneumatological” contribution to the ongoing conversation about eco-justice. To do so, it draws on classic Lutheran understandings of creation and grace, even as it calls for a more expanded—and more deeply biblical—understanding of the Holy Spirit's presence and activity throughout all of creation. © 2016 Wiley Periodicals and Dialog, Inc.
Paid
Keywords: Africa; Lutheran theology; eco-justice; eco-theology; pneumatology